Effects of Input Parameters on the Hole Quality During the Drilling of Al Metal Matrix Composites - Alokesh Pramanik; Animesh Kumar Basak (Designs)
The extensive industrial applications of aluminum (Al) metal matrix composites (MMCs) require optimal drilling conditions in the manufacturing industries. The effects of drilling variables, for instance, the point angle, spindle speed and feed rate on torque, thrust force, burr, surface quality, and dimensional errors were analysed while producing holes in MMC. The results showed that the torque and thrust force decreased with an increase in point angle and speed but increased with the rise in feed rate. Similar trends were also noticed for the chip thickness as these parameters vary. The burr height, circularity, and diameter error at the exit and entrance of the workpiece material were highly impacted by the point angle. In addition, the feed rate showed a strong influence on torque, burr height at the exit of the workpiece, and chip thickness. Thrust force and circularity as well as the diameter error at the exit of the workpieces were highly affected by the feed rate. The variation in surface roughness was not significant with the variations in the parameters considered in this investigation.